Assessing the influence of employee characteristics on their perceptions about retention and endorsement - Ramirez, Rita (Kansas State University, 2021)
Traditional strategies that have attracted and retained employees in the past will be challenging as the demographics of the workforce entering is drastically changing. Business success is dependent on full access to applicable data for quick decision making and strategy development. The Human Resources department at a specialty foods company wanted to ensure that it was preparing for the upcoming trends that would make them the employer of choice as it felt it has been in years past. The company is very proud of its culture and high employee retention rates, however after an analysis of its current multigenerational workforce, the organization contemplated whether it would continue to have a competitive advantage that retains and attracts employees in the future. The study was meant to examine what strategies the company may implement to increase its ability to retain its employees and enhance its attractiveness to candidates as a choice place to work. The Human Resources department wanted to use raw data obtained from an employee survey to further analyze responses in order to determine if demographic factors influenced responses. However, due to limitations in procurement of full data, the study produced a “synthetic” dataset for assessing the influence of three different employee characteristics: Tenure, Activity/Location, and Gender. There were two statements of interest that were analyzed: “I want to work here for a long time” and “I would strongly endorse my company to friends and family as a great place to work”. These two statements would give insight on retention intent and a sense of corporate culture and employee engagement. If employees truly had an outstanding employee experience they would want to work for the company for a long time and become personal endorsers to their friends and family which is the most trusted form of endorsed marketing. To generate the data, the average responses and their standard deviations for each statement and each employee characteristic associated with the response were estimated using Bernoulli Distribution protocol. Due to the scoring method and restricted data provided, there were expected limitations of the results that would be produced as they are based on possibility of responses. The synthetic data was used to estimate logit regression models seeking to determine the extent to which employee characteristics influences their responses to the two statements of interest. The regression models only declared that the difference between those who have 20+ years of tenure desire to work for the company for a long time and new hire’s desire to work at the company for a long time is statistically significant (p<.05). All other variables were not statistically significant. The analysis conducted was to provoke management to make the necessary investments in getting the essential data to facilitate effective management of employees’ attitude towards the two critical statements based on their characteristics. Having the raw data would have allowed more granular substance to run regression models to explore statistical significance of how different demographic variables influences responses. It also leads to developing in-depth exploration of other factors that influence employees in their attitudes about the company’s culture to enable the Human Resources Department to develop more effective interventions for prompting the required behaviors to support the aspirational culture environment in the company.
Keywords: Agribusiness; Employee retention; Employee perception; Millenial; Culture; High performing culture